2021
DOI: 10.1101/2021.06.11.21258690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 is associated with changes in brain structure in UK Biobank

Abstract: There is strong evidence for brain-related pathologies in COVID-19, some of which could be a consequence of viral neurotropism. The vast majority of brain imaging studies so far have focused on qualitative, gross pathology of moderate to severe cases, often carried out on hospitalised patients. It remains unknown however whether the impact of COVID-19 can be detected in milder cases, in a quantitative and automated manner, and whether this can reveal a possible mechanism for the spread of the disease. UK Bioba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 85 publications
9
90
1
7
Order By: Relevance
“…More recently concern has been raised that such effects may also extend to adolescents and children -a group generally considered to be at 'low risk' from Covid-19 infection [20]. A range of possible pathophysiologies have been identified, including direct neuroinvasion [21], viral persistence and chronic inflammation [22], neuronal injury or toxicity and glial activation [21], microvascular injury [23], activation of autoimmune mechanisms [24], and Lewy body production [25] amongst others, with imaging studies demonstrating a differential loss of grey matter in Covid patients in a number of key brain regions [26].…”
Section: Introductionmentioning
confidence: 99%
“…More recently concern has been raised that such effects may also extend to adolescents and children -a group generally considered to be at 'low risk' from Covid-19 infection [20]. A range of possible pathophysiologies have been identified, including direct neuroinvasion [21], viral persistence and chronic inflammation [22], neuronal injury or toxicity and glial activation [21], microvascular injury [23], activation of autoimmune mechanisms [24], and Lewy body production [25] amongst others, with imaging studies demonstrating a differential loss of grey matter in Covid patients in a number of key brain regions [26].…”
Section: Introductionmentioning
confidence: 99%
“…For the COVID-CNS project, it provides insights that can guide the design of harmonisation strategies for the project. More broadly, the study is of relevance to the expanding number of studies utilising multi-modal imaging protocols derived from the UK Biobank, including a number of additional studies focused on the neurological impact of COVID-19 (Douaud et al, 2021;Raman et al, 2021) . Overall, our results demonstrate generally good to excellent levels of between-site reliability of imaging derived phenotypes estimated across a wide range of brain MRI modalities in data collected from 4 UK sites participating in a national COVID research consortium.…”
Section: Discussionmentioning
confidence: 99%
“…T2 FLAIR and swMRI sequences were slightly modified from UKB standards in order to more closely match corresponding sequences in the C-MORE protocol. A multi-post label delay (PLD) 3D-GRASE ASL sequence (Günther et al, 2005) was used identically to that planned to be adopted by UKB COVID study (Douaud et al, 2021) (different to the 2D multi-slice sequence used in C-MORE); a single delay ASL sequence was additionally used to match the ASL imaging pulse sequence of the GE scanner.…”
Section: Scanners and Scanning Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…There were reports of neurological symptoms, and a recent imaging study from the UK Biobank (pre-peer reviewed) demonstrated volume loss in the left parahippocampal, orbitofrontal and insular regions, even after mild COVID- 19 infection, showing that the central nervous system is also affected by COVID-19. These neurologic effects may involve the RAS [5], especially since ACE2 is expressed in neurons and microglia (Figures 1 and 2). Agtr2-Type-2 angiotensin II receptor.…”
Section: The Renin-angiotensin System (Ras) In the Brainmentioning
confidence: 99%